Assessing livestock husbandry, gendered decision-making and dietary quality among smallholder households in rural Timor-Leste - Bonis-Profumo, Gianna (Charles Darwin University, 2019)
Presented by Gianna Bonis-Profumo (Charles Darwin University), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.